Design and Planning of the Sara Island Tourism Destination, Taulad Regency, North Sulawesi - Lagarense, Helni Desty Yanice; Laluas, Efraim; Pramesti, Dinar Sukma (Institut Pariwisata dan Bisnis Internasional, 2025)
Sara Island in the Talaud Islands Regency holds great potential for sustainable marine tourism due to its pristine beaches and rich biodiversity, yet its development is constrained by limited infrastructure, accessibility, and coordination. This study aims to design a conceptual master plan for sustainable tourism development using the AFITH-based framework (Attraction, Facility, Infrastructure, Transportation, Hospitality) integrated with Community-Based Tourism (CBT) principles. A qualitative descriptive method was applied through field observations, interviews, and document analysis, with data processed using content analysis and triangulation for credibility. The results present an integrated master plan featuring eco-friendly facilities such as solar lighting, waste segregation, sanitation areas, and relaxation zones, emphasizing participatory and environmentally responsible planning. The findings show that sustainable island tourism depends on balancing infrastructure development, conservation, and community involvement. This research provides a theoretical contribution to sustainable destination design and offers practical implications for local policy, recommending the establishment of a Destination Management Organization (DMO) and future mixed-method research to assess environmental and economic feasibility.